Major signaling pathways in intestinal stem cells - Vanuytsel, Tim; Senger, Stefania; Fasano, Alessio; Shea-Donohue, Terez (Biochimica et biophysica acta, 2013)
The discovery of markers to identify the intestinal stem cell population and the generation of powerful transgenic mouse models to study stem cell physiology have led to seminal discoveries in stem cell biology. In this review we give an overview of the current knowledge in the field of intestinal stem cells (ISCs) highlighting the most recent progress on markers defining the ISC population and pathways governing intestinal stem cell maintenance and differentiation. Furthermore we review their interaction with other stem cell related pathways. Finally we give an overview of alteration of these pathways in human inflammatory gastrointestinal diseases. We highlight the complex network of interactions occurring among different pathways and put in perspective the many layers of regulation that occur in maintaining the intestinal homeostasis. Understanding the involvement of ISCs in inflammatory diseases can potentially lead to new therapeutic approaches to treat inflammatory GI pathologies such as IBD and celiac disease and could reveal the molecular mechanisms leading to the pathogenesis of dysplasia and cancer in inflammatory chronic conditions. This article is part of a Special Issue entitled Biochemistry of Stem Cells. ► The two stem cell populations in the small intestine have distinct markers. ► Critical pathways in the intestine are Wnt, Notch, Hedgehog, BMP, and Hippo/Yap. ► Alterations of stem cell signaling pathways occur in gut inflammatory pathologies.